Evaluation of Mandibular First Molars’ Axial Inclination and Alveolar Morphology in Different Facial Patterns: A CBCT Study - Ferreira, Marcos Cezar; Freitas, Karina Maria Salvatore de; Herrera-Sanches, Francyle Simões; Santos, Patrícia Bittencourt dos; Garib, Daniela; Janson, Guilherme; Freitas, Marcos Roberto de (European Journal of Dentistry, 2020)
Objective The purpose of this study was to evaluate and compare the axial inclination of the mandibular first molars and their respective bone morphology among individuals with different facial patterns.Materials and Methods The sample comprised the cone beam computed tomographies (CBCTs) of 58 subjects divided into three groups according to the facial patterns: 18 brachyfacial (Group 1), with a mean age of 21.58 years; 23 mesofacial (Group 2), with a mean age of 19.14 years; and 17 dolichofacial subjects (Group 3), with a mean age of 19.09 years. Eight variables were evaluated on CBCT scans of each subject: buccal and lingual mandibular height, cervical and middle mandibular width, inclination of mandibular body, inclination of the mandibular molar buccal surface, molar width, molar angulation and tooth/bone angle. Intergroup comparisons were performed with one-way analysis of variance followed by Tukey tests.Results Buccal mandibular height presented statistically significant difference in the three facial patterns. Lingual mandibular height and mandibular inclination showed to be statistically and significantly smaller in brachyfacial subjects than in the other two groups. Mandibular width presented a statistically significant difference between brachyfacial and mesofacial groups. Negative correlations could be observed between the facial pattern and the buccal and lingual mandibular heights and inclination of the mandibular body.Conclusion Buccal mandibular height was significantly and progressively larger in brachyfacial, mesofacial, and dolichofacial subjects. Lingual mandibular height was significantly smaller in brachyfacial than in mesofacial and dolichofacial subjects. Mandibular width was significantly thicker in brachyfacial than in mesofacial subjects. Brachyfacial subjects had smaller mandibular inclination than mesofacial and dolichofacial subjects.
Keywords: cone beam computed tomography; mandible; molar